PENGARUH UKURAN PERUSAHAAN DAN RETURN ON ASSET TERHADAP PRICE TO BOOK VALUE PT GARUDA INDONESIA YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Meilin Veronica (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2024)
This study aims to analyze the effect of company size and return on assets on the price to book value of PT Garuda Indonesia for the 2018-2021 period. The data source of this research is secondary data in the form of quarterly financial reports obtained from the official IDX website and other supporting sources. The data analysis method used is the classical assumption test and multiple linear regression. The results of this study indicate that partially only company size (X1) effects on price to book value (Y). Meanwhile, return on assets (X2) has no effect on price to book value (Y). This research is expected to provide benefits for companies to increase their price to book value through company size and return on asset ratio